Impacts of oil and gas internal risk factors on project success : Moderating role of government support - Ajibike, Waliu Adeniyi; Adeleke, Adekunle Qudus; Muuka, Gerry Nkombo; Bamgbade, Jibril Adewale; Mohd Ridzuan, Darun; Moshood, Taofeeq Durojaye (Australian Institute of Quantity Surveyors, 2022)
Organisational internal risk factors, which include management, material, finance and design risk factors, affect oil and gas construction projects’ success in emerging nations, in which Malaysia is no exception. The purpose of this study is to examine the effect of these internal risk factors and government support on oil and gas projects. Data were collected from 61 employees of oil and gas firms within Peninsular Malaysia using a questionnaire survey. The data were analysed using the structural equation modelling (SEM) technique. The results revealed that all the exogenous variables (design risk, management risk, financial risk and material risk factors and government support) significantly impact project success. Although the insignificant and unsupported hypotheses in this study are not unconnected with the current COVID-19 pandemic, which made the government shift attention to medical facilities projects. This study implies that managerial capability is critical in managing risks and ensuring the successful delivery of projects. As a result, project managers are expected to be on top of the triple constraint’s essential qualities, which increase the chance of project success. They must be aware of any changes to the essential characteristics, whether unexpected or desired. The study developed an all-inclusive framework that can assist stakeholders within the industry and academia in mitigating internal risk factors in ensuring the success of projects.